Student Educational Responsibility: ACase Study of Emotional Response to International Education - Bryan J. Hains; Kristina G Ricketts; Jonathan A Tubbs (Journal of International Agricultural and Extension Education, 2012)
This study focuses on student emotional reactions toward new events or stimuli within a learner-centered, international education course. Using the primary tenets of appraisal theory, researchers analyzed novel stimuli, as identified by the students, and students’ emotional reactions toward each stimulus. Participants were immersed into two separate Scottish island communities for a 22-day period. The primary course objective included students developing leadership skills associated with community development while working with ruralScottish communities.Results indicated that students experienced a wide range of emotions associated with multiple stimuli. Identified stimuli were dichotomized into two categories, the international immersion process as well as the shift in educational responsibility from instructor to student. Emotional magnitude and coping mechanisms differed from student to student. Post international study reflections indicated that students experienced a deeper learning experience when using a learner-centered approach to international education.
Keywords: Higher Education; Experiential Learning; Student Issues; Qualitative Research